2012
DOI: 10.1152/ajpregu.00048.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial core temperature on hyperthermic hyperventilation during prolonged submaximal exercise in the heat

Abstract: Nishiyasu T. Effect of initial core temperature on hyperthermic hyperventilation during prolonged submaximal exercise in the heat. Am J Physiol Regul Integr Comp Physiol 302: R94 -R102, 2012. First published September 28, 2011 doi:10.1152/ajpregu.00048.2011.-We investigated whether a core temperature threshold for hyperthermic hyperventilation is seen during prolonged submaximal exercise in the heat when core temperature before the exercise is reduced and whether the evoked hyperventilatory response is affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 42 publications
9
27
0
Order By: Relevance
“…Because oxygen uptake and blood lactate concentrations remain relatively constant during such exercise and are similar under hot and thermoneutral conditions (18,32), these results suggest that it is not metabolic factors, but the elevation in body temperature that mediates the increase in V E . During prolonged exercise, the elevation in core temperature, but not skin temperature (18,46), leads to an increase in V E beyond what would be expected from metabolic demand.…”
mentioning
confidence: 95%
“…Because oxygen uptake and blood lactate concentrations remain relatively constant during such exercise and are similar under hot and thermoneutral conditions (18,32), these results suggest that it is not metabolic factors, but the elevation in body temperature that mediates the increase in V E . During prolonged exercise, the elevation in core temperature, but not skin temperature (18,46), leads to an increase in V E beyond what would be expected from metabolic demand.…”
mentioning
confidence: 95%
“…On the other hand, White and Cabanac 7) reported that during incremental exercise, there is a core temperature threshold for hyperventilation around a tympanic temperature of 37.0-37.7 °C or a Tes of 37.5-37.9 °C, while Beaudin et al 8) and Sancheti and White 9) reported the Tes threshold for hyperventilation during incremental exercise to be around 37.1-38.2 °C. In addition, after pre-cooling subjects in cold water (18°C) to decrease body temperature enough to cause a 1°C drop in Tes, Tsuji et al 6,10) found that there is a Tes threshold for hyperventilation around 37°C during prolonged steadystate light and moderate intensity exercise (25% and 50% of peak oxygen uptake [V ・ O2peak], respectively). Above this threshold, V ・ E and respiratory frequency increased in proportion to the increase in Tes 3,5,6,10) (Fig.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
“…In addition, after pre-cooling subjects in cold water (18°C) to decrease body temperature enough to cause a 1°C drop in Tes, Tsuji et al 6,10) found that there is a Tes threshold for hyperventilation around 37°C during prolonged steadystate light and moderate intensity exercise (25% and 50% of peak oxygen uptake [V ・ O2peak], respectively). Above this threshold, V ・ E and respiratory frequency increased in proportion to the increase in Tes 3,5,6,10) (Fig. 2), though no increases in tidal volume were seen.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
See 2 more Smart Citations